English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

ln(r^9s^3 √r^9s^7)

^ = raised to power.
√ = Square root of all terms that follow this sign

2007-02-11 17:07:39 · 2 answers · asked by Tazzzy 1 in Science & Mathematics Mathematics

2 answers

ln{r^9 s^3 √(r^9s^7)} = ln{r^[9 + (9/2)]s^[3 + (7/2)]}
= ln{r^(27/2) s^(13/2)} = ln{r^(27/2)} + ln{s^(13/2)}
= (27/2)(ln r) + (13/2)(ln s)

2007-02-11 18:10:51 · answer #1 · answered by Northstar 7 · 0 0

Simplify.

ln{r^9 * s^3 * r^9/2 * s^7/2}

ln{r^27/2 * s^13/2} = ln{r^27/2} + ln{ s^13/2}

trivial after that...

2007-02-12 01:26:07 · answer #2 · answered by Phoenix 1 · 0 0

fedest.com, questions and answers